Mulla Sadra and Metaphysics: Modulation of Being by Sajjad H. Rizvi (London and New York: Routledge, 2009. hbk. 222 pages) (American Journal of Islam and Society, 2011)
Mullā Ṣadrā and Metaphysics: Modulation of Being appears at a time whenthe study of Ṣadr al-Dīn al-Shīrāzī’s philosophy has reached a critical mass.Critical editions of Shirazi’s works are available, and there are numerousstudies on aspects of his thought. Rizvi has done an excellent job of synthesizingthis information, examining it critically and building on it to pushSadrian studies forward. The philosophical question that Rizvi explores inthis book is: “[h]ow can we reconcile the vision of the unity in existenceand the quest for a singular explanation for reality with our everyday, phenomenalexperience of plurality and multiplicity?” (xi). Rizvi approachesthis question both as a philosopher and a historian of philosophy.The aim of this study is to examine Shirazi’s central philosophicalidea—the modulation of being—and to use this idea to understand hisphilosophy. Whereas most studies on Shirazi have focused on Kitāb al-Mashā‘ir or al-Ḥikma al-‘arshīya, Rizvi focuses on the section on metaphysicsin Shirazi’s most important work Al-Ḥikma al-muta‘ālīya, or simplythe Asfār. There are two major theses in this book. One, “tashkīk is ahermeneutic concept which describes the threefold division of being andits gradation,” and two, “gradation and modulation occur in each mode ofbeing” (3). As Rizvi points out, “being in expression” is the foundation ofShirazi’s semantic theory; “mental being” is about epistemology and psychology;and “actual being” covers metaphysics. “Modulation,” then, isthe axis around which different branches of Shirazi’s philosophy revolve ...